A comparison of training, injury, illness, sleep, wellbeing and stress between developing elite and recreational athletes - Lowery, M.; Oliver, S. J.; Roberts, R.; Barwood, C.; Dunn, E.; Langham-Walsh, E.; Holliss, B.; Wraith, L.; Woodman, T.; Lawrence, G.; Gottwald, V. M.; Hardy, J. (European Journal of Sport Science, 2025)
The impact of National Governing Body talent development programmes on injury, illness, sleep, wellbeing and stress of developing elite athletes (DEA) is poorly understood. Therefore, we examined differences between age-matched DEA (n = 42, 25 females; Mage = 21.0; SD = 2.5) and recreationally active athletes (RAA, n = 79, 56 females; Mage = 21.2; SD = 2.8) on these variables over 14 weeks of training using a weekly online monitoring tool. Compared to RAA, DEA completed a greater proportion of planned training and competition without health problems or reducing training volume. Despite training more hours (DEA M = 17.1; SD = 5.1, RAA M = 6.0; SD = 3.2, p < 0.001), DEA reported similar recovery, higher readiness to train, more sleep, better sleep quality, higher wellbeing (DEA M = 68%; SD = 15, RAA M = 56% SD = 16, p < 0.001), lower stress and fewer injuries, resulting in fewer days lost to injuries than RAA (DEA M = 0.4; SD = 1.5, RAA M = 2.5 SD = 6.7, p = 0.01). There was no difference between DEA and RAA in the prevalence of illness or days lost due to illness. In conclusion, despite a greater training and competition load, DEA reported better health and wellbeing than RAA, suggesting the increased demands of National Governing Body talent development programmes may not adversely affect health. These findings also highlight the benefits and importance of talent development systems undertaking a holistic and multidisciplinary approach to athlete monitoring.